Effect of Synthesis Method and Nickel-Copper Loading on Ni-Cu-Al Catalysts for Production of Hydrogen Via Ethanol Steam Reforming - Abdullah Irankhah; Sepideh Ghafoori; Atieh Ranjbar (Iranian Journal of Chemical Engineering)
In the present work, the effect of synthesis method (simultaneous impregnation and coprecipitation) and copper to nickel active phases loading were investigated in Ni-Cu-Al catalysts. The water/ethanol molar ratio of 6 and gas hourly space velocity (GHSV) of 20000 hr-1 were used in all the experiments. The catalysts were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD) and thermogravimetric analysis (TGA) techniques. The catalytic activity results revealed that 13Ni-6Cu/γ-Al2O3 impregnated catalyst was more active than co-precipitated one (13NiO-6CuO-81Al2O3) in the same amount of compositions of active metals and Al2O3, but by increasing the active phases (Cu and Ni) loading in co-precipitated catalysts (24NiO-31CuO-45Al2O3, 31NiO-24CuO-45Al2O3, 40NiO-15CuO-45 Al2O3 and 47NiO-8CuO-45Al2O3), they achieved a better performance than 13NiO-6CuO-81Al2O3 catalyst. The 40NiO-15CuO-45Al2O3 catalyst showed 99% ethanol conversion, as well as 303 hydrogen yield and 4% CO selectivity at 470oC. SEM images revealed agglomerated particles for the samples with high Al2O3 content and with increasing the active phase content in the catalyst the particle sizes decreased. The 40NiO-15CuO-45Al2O3 showed smallest particle size among the catalysts.